ANATOMI TUJUH JENIS KAYU DARI MALUKU UTARA (Anatomy of Seven Wood Species from North Maluku) - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1993)
Gross and anatomical fentures  of seven wood species from North Maluku were observed and described for  identification purposes. Fibre dimension were also measured and evaluated for  their suitability for pulp and paper.The colour of wood ranges from   white to brown, mostly plain without figure.  Only one species has decorative figure  on its surface, that is Dracontomelon sp.  So it is recommended for fancy veneer of plywood or for furniture.The main anatomical features  of each wood species are as folows : a) vessels are exlusively solitary and aranged in radial groups in Calophyllum inophyllum; a few  vesels are radially multiple up to seven cells in Heritiera sp.;  (b scalariform perforation plates present mainly  in  Elmerillia  sp.and   rarely  in  Horsfieldia  sylvestris;  c) parenchymma  bands  are present   in  Calophyllum  inophyllum, Horsfieldia   sylvestris and Elmerillia sp.  : d) rays uniseriate   in Calophyllum inophyllum;    e).fiber septate in Dracontomelon sp.; f) axical intercelular  canals are present  in Hopea sp.  and Shorea koordersii;  g) oil cells in Elmerillia sp.  and taniniferous  tube in Horsfieldia sylvestris.Five species contain fibres  with medium quality  (Horsfieldia sylvestris,   Dracontomelon  sp.,   Heritiera sp.,  Shorea  koordersii  and Elmerillia sp.). other species contain fibres with poor quality.